Studi Perbandingan Komposisi Campuran Zeolit dengan Resin Kation terhadap Nilai Kesadahan, Konduktivitas, dan pH Air pada Pengolahan Air Lunak - Yusdianto, Yusdianto; Thamrin, Siti Nurhalisa; WIJAYANTO, HENDI LILIH (Politeknik AKA Bogor, 2024)
Morowali is an industrial area engaged in metal production. Steel production is closely related to the cooling process, especially equipment cooling. In the cooling process, water is used as a cooling medium. The water used in the cooling process must be free of minerals, especially those that can damage the cooling tower equipment. Some analytical test parameters include pH, electrical conductivity, and hardness. To obtain cooling water that meets the standards, a treatment process is required. One of the treatment processes used is the ion exchange method using cation resin media, but there is a decrease in the lifetime of cation resin. One alternative material that can be used as an ion exchange medium is zeolite. Therefore, one solution that can be tried is to use a mixture of composition between cation resin and zeolite as an ion exchange medium. The research was conducted using a simple simulator tool by varying the composition of the mixture between zeolite combined with cation resin with the same initial sample and water flow rate. From the test results that have been carried out, the percent value of hardness removal for samples R100:Z100; R75:Z25; R50:Z50; R25:Z75; and R0:Z100 are 85.45%; 50.91%; 40.91%; 14.54%; 5.45%, respectively. The pH values were 7.37; 7.85; 7.80; 7.79; 7.58; 7.43, respectively. And the conductivity values are 612